Implementation of Communicative and Interactive Method in Strengthening Students' Speaking Skills through English Club Activities at MTs Muslimat NU Palangka Raya - Siliwangi, Diah Puji; Erliana, Santi (PT. Amirul Bangun Bangsa, 2025)
This article discusses about community service activity that aims to implement communicative and interactive methods as an effort to strengthen students' speaking skills through English Club activities at MTs Muslimat NU Palangka Raya. This activity is designed to provide a more active and enjoyable learning experience and provide space for students to practice using English more naturally outside of formal learning. The activity is carried out through several stages, starting from an introduction to the activity, mentoring during animal-themed